Program uor Empowering the Role of Religious Leaders as Renewal Agents for Community Health in the Covid-19 Pandemic - Oktovina Mobalen; Elisabeth Samaran; Laurdes Situmorang (Universitas Malahayati Lampung, 2023)
ABSTRACT The handling of Covid-19 cases must be carried out with the support of all parties, not only the responsibility of health workers because Covid-19 is a public health problem. The role of religious leaders is increasingly significant in the era of advances in information technology. The ease of influence and the role of religious leaders in controlling change significantly influence society. The primary purpose of community service activities for religious leaders is to act as an agent of health reform in the community during the Covid-19 Pandemic. This method of community service is socialization, training, and advocacy of the approach through the department of religion, and empowerment of religious leaders in the Sorong City area, Masimsa sub-district. Giving pocketbooks. The Role of Religious Leaders as Agents of Reform for Health in the Community During the Covid-19 Pandemic. Providing pocketbooks. On Empowering the Role of Religious Leaders as Agents of Reform for Health in the Community in the Covid-19 Pandemic in 2022